Computational challenges in modeling gene regulatory events. Issue 5 (19th October 2016) - Pataskar, Abhijeet; Tiwari, Vijay K.
ABSTRACT: Cellular transcriptional programs driven by genetic and epigenetic mechanisms could be better understood by integrating "omics" data and subsequently modeling the gene-regulatory events. Toward this end, computational biology should keep pace with evolving experimental procedures and data availability. This article gives an exemplified account of the current computational challenges in molecular biology.